Features of The Family Context in the Emergence of Anxiety in Adolesence - Hasanova, Gulnara (2020)
The article reveals the current problems of the modern family, in which the relationship and behavior of parents are a factor in the formation of emotional instability and anxiety in adolescents. At the present stage of development of society, the study of psychological and pedagogical conditions for reducing the level of anxiety in adolescents is relevant, since a high level of anxiety reduces school performance, has a negative impact on the development and formation of a teenager's personality. In this regard, the study of this problem and the development of programs aimed at reducing anxiety is relevant. Comprehensive measures carried out by psychologists with parents and students make it possible to organize a timely diagnostic examination, followed by the introduction of corrective and preventive programs aimed at creating a favorable psychological climate, both in the school community and in the families of teenagers. The experimental part of the study revealed the relationship between the type of family education and the development of anxiety in this age group. High levels of anxiety were identified on indicators of General school anxiety, the relation between the anxiety scale and the "authoritarian giperstimulyatsia" (for methodology A. Y. Varga and V. V. Stolin), and also high indicators on scales "the instability of parenting style" and "dominant giperprodukcia" (ASV method E.Eidemiller). The results of our empirical research allow us to conclude that the psychological climate in the family is the most important factor in the favorable psycho-emotional development of children of this age category. The use of the wrong style of family education encourages the formation of emotional instability and anxiety in adolescents, which affects the overall emotional background and the learning process.